PELATIHAN PENGGUNAAN GAFE DAN KAHOOT SEBAGAI MEDIA PEMBELAJARAN DI SMP YPPK YOANES XXIII MERAUKE - Anderias Henukh; Merta Simbolon (Musamus University, 2022)
The COVID-19 pandemic forces us to innovate in learning. However, the lack of awareness of teachers to use technology in learning, especially using Google Apps For Education and Kahoot as Gamification-based learning media. There is no special training related to learning using technology, especially using Google Apps For Education and Kahoot. There is not enough knowledge and skills regarding Google Docs, Google Sheets and Google Slides as a medium to work together on a virtual worksheet effectively and efficiently. Teachers still use quizzes, assignments, and written tests on paper that are printed and distributed manually to students so that they are not accustomed to working on these instruments using computers or cellphones based on Android or IOS even though this is very much needed at this time. The method used for this service activity is socialization, training, mentoring, monitoring, and evaluation. The results of the service showed that the teachers experienced an increase in knowledge and skills after participating in the service. Keywords: Training, GAFE, Kahoot, Learning Media